Advances in Psychosomatic Medicine 2008
DOI: 10.1159/000126628
|View full text |Cite
|
Sign up to set email alerts
|

Drugs of Abuse and Sexual Functioning

Abstract: The use of mind-altering substances can be found in very different cultures and traced back thousands of years; the same is true for the searching of drugs that could increase sexual functioning. In this text, we explore the relation between drugs of abuse and sexuality in three domains: drugs and sexual dysfunctions, drugs and risky sexual behavior and drugs used as sexual aids. Although some drugs can increase sexual response in the early stages of the addiction career, particularly in those with a previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 61 publications
0
35
0
5
Order By: Relevance
“…Virtually, alcohol and illicit drugs are known to have inhibitory effects on libido and ejaculation. 40,50,60 Psychoactive substance dependence is a predominantly male activity. Illicit drug use is even more prevalent among young people than in older age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtually, alcohol and illicit drugs are known to have inhibitory effects on libido and ejaculation. 40,50,60 Psychoactive substance dependence is a predominantly male activity. Illicit drug use is even more prevalent among young people than in older age groups.…”
Section: Discussionmentioning
confidence: 99%
“…58 Dopamine has been implicated as facilitator and serotonin an inhibitor of sexual function. 59,60 There are long-term psychiatric and physical problems associated with MDMA use. Neurotoxicity induced by MDMA is cumulative and is related to the dose and frequency of drug use.…”
Section: ) Opioidsmentioning
confidence: 99%
“…[14][15][16] There are several reasons smoking affects sexual function. 6,13 First, nicotine is considered a strong vasoconstrictor and therefore can significantly reduce blood flow to the male and female genitals during sexual activity. 6,13 In an excellent review, it was reported that nicotine, in fact, that can significantly reduce vasoactive substances, such as endothelium-derived relaxing factor, nitric oxide, prostaglandin, prostacycline, and thromboxane, in the vascular endothelium of the male and female genital tract.…”
Section: Tobaccomentioning
confidence: 99%
“…Furthermore, there has been continued interest in studying the effect of drug addiction on human sexual function. 6 This article examines the effects of drugs of abuse on male and female sexual function. Because of the very wide range of drugs of abuse, the most common of them, namely, alcohol, cannabis, cocaine, tobacco, amphetamines, opioids, and antidepressant drugs, are focused on.…”
Section: Introductionmentioning
confidence: 99%
“…Although some drugs can initially increase sexual response, particularly in those with previous sexual problems, the chronic use of substances tends to deteriorate all stages of sexual function in both male and female drug users [3][4][5] . In line with this evidence, a very high prevalence of sexual dysfunction was recently reported in association with substance use disorders in a Brazilian sample, with a significant correlation between sexual problems and the severity of drug use [6] .…”
Section: Introductionmentioning
confidence: 99%